Learning Resource Center Organizational Programs and Facilities - Nugraheni Widiastuti; Mulik Cholilah; Abd Rozid; Retno Danu Rusmawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Organization of Learning Resource Centers (OLRC) acts as a supporting facility for the effectiveness and efficiency of the learning process, designed to provide convenience to students and teachers in utilizing learning resources. This research uses the literature study method by collecting information from various sources such as books, articles, journals, and relevant scientific papers. The purpose of the research is to find out the LRC program and facilities that support the effectiveness and efficiency of learning. The results showed that the LRC program involves at least three activities, namely Learning System Development, Learning Multimedia Development, and Learning Resource Needs Services. LRC, also known as media center, functions as an educational institution that provides facilities for planning, production, operation, and follow-up actions in the development of learning systems with physical and digital facilities following the times and technology.